SMEs E-Commerce Functional Value and Brand Performance: The Role of Internal and External Stimuli - Masran Tamin; Azaze Azizi Abdul Adis (Faculty of Business, Economics and Accountancy Universiti Malaysia Sabah, 2023)
The rapidly evolving digital landscape has positioned small and medium enterprises (SMEs) at the forefront of e-commerce growth. Shifting to online business has recently been identified as a strategic resource for SMEs’ competitive advantage. Thus, e-commerce and brand performance are integral components of SMEs' online business strategies. This study adopts the S-O-R framework as the theoretical foundation to examine the impact of both external and internal Stimuli (i.e., relative advantage, compatibility, government support, and supplier pressure) that trigger SMEs cognitive and affective states, i.e., Organism (e-commerce functional value), and Response (brand performance) in SMEs online business. Survey data were gathered from 152 Malaysian SMEs online business. Data were analyzed using SmartPLS software. The study discovers the significant and insignificant relationships between relative advantage, compatibility, government support, supplier pressure, e-commerce functional value and brand performance. As e-commerce continues to redefine the SMEs online business landscape, this research offers valuable insights for SMEs seeking to leverage e-commerce effectively and enhance SMEs brand performance.